Among digitized manuscripts - Lit, Lambertus Willem Cornelis van (Brill, 2020)
Manuscript World, Print World, Digital World – The Digital Materiality of Digitized Manuscripts – Digitized Manuscripts and Their Repositories, an Ethnography – Paleography: Unraveling Mysterious Symbols on a Computer – Philology: Standards for Digital Editing – Digital Cataloging: the Geyer Collection at the Monastery of Sankt Florian – Codicology: Automated Analysis Using Python and OpenCV – A Digital Orientalist
Keywords: Manuscripts / Data processing; Manuscripts / Digitization; Codicology / Data processing; Philology / Data processing; Paleography / Data processing; Islamic civilization / Manuscripts / Library resources; Digital humanities; Paläographie; Philologie; Digitalisierung; Handschrift; Handschriftenkunde